ASPEK SOSIAL BUDAYA MASYARAKAT NELAYAN DALAM MENDUKUNG PROGRAM EKOWISATA BAHARI DI KEPULAUAN SERIBU - Indarjani, R. (MAJALAH ILMIAH WIDYA, 2012)
Socio-cultural approach in relation to sustainable economic development is a necessity. The Thousand Islands regency located at 45 km of northern Jakarta on the 106Âº20â00â East Longitude(EL)Â to 106Âº57â00â ELÂ and 5Âº10â00â South Latitude (SL) to 5Âº57â00â LS, where marine ecotourism as a basis of regional development policy, which certainly has implications on social and cultural life of their society. This study is intended to mitigate the impact of tourism on the social life of fishing communities by looking at the potential factors that can be developed, as well as the factors that threaten the survival of the tourism program. The research method was qualitative descriptive analysis where the results generated should be viewed as a local phenomenon. The result show that the identification of social and cultural factors, it will be formulated the control mechanism of social and cultural impacts in supporting of tourism activities in the Thousand Islands.